A COMPARISON OF METAL ELEMENTS ON LIMONITE AND SAPROLITE LAYERS IN NICKEL MINING FRONT IN HUKO-HUKO AREA, POMALAA DISTRICT, KOLAKA REGENCY: PERBANDINGAN UNSUR LOGAM PADA LAPISAN LIMONIT DAN SAPROLIT DI FRONT PERTAMBANGAN NIKEL DI DAERAH HUKO-HUKO KECAMATAN POMALAA KABUPATEN KOLAKA - Liber, Muhammad Jagad Sirollahi (ReTII, 2021)
ABSTRACT Laterite nickel sediment especially on layers’ limonite which are mined made as a product does not have economical valued, where this material was only made as a mined road hoarder or stacked and left useless without further handling. So, it is necessary to do a research to determine the content and distribution of metal elements in front nickel mining on layer limonite in Huko-Huko village, Sub district Pomalaa in Southeast Sulawesi province by using the method SEM-EDX (Scanning Electron Microscopy-Energy Dispersive x-ray) with the results obtained from the analysis of seven samples tested using SEM-EDX get that the highest element in the sample material in front nickel mining are Fe is 50.60%, O is 44.90%, Al is 5,40%, Cr is 2.22%, Mn is 1.63% , Mg of 8.19%, Si is 13.11%, and Ni is 2.27%.